Examination of the legal framework of kidnapping and hostage-taking in Nigeria (2018)
The crimes of kidnapping and hostage-taking in Nigeria have evolved from being means of calling the attention of the government towards the marginalization of Niger-Delta Region, to organised crime committed for ransom that violate the fundamental human right of liberty and freedom of movement of a person which pose vital challenge to the security of lives of Nigerian citizens. Hence, this study looks at the history, statistics /incidents, targets, causes and types of kidnapping. It goes further to examine the extant laws of kidnapping and hostage-taking in Nigeria and their lacunae. The study also discusses some challenges of kidnapping and recommends the necessity of making a new law or amending the existing one by filling up some lacunae particularly the punishment section. The government, security agents, and the Nigerian citizens are sensitized to be more proactive, vigilant and security conscious in combating kidnapping and hostage-taking for ransom in Nigeria.